Synaptic Determinants of Rett Syndrome - Boggio, Elena M.; Lonetti, Giuseppina; PIzzorusso, Tommaso; Giustetto, Maurizio (Frontiers in Synaptic Neuroscience, 2010)
There is mounting evidence showing that the structural and molecular organization of synaptic connections are affected both in human patients and in animal models of neurological and psychiatric diseases. As a consequence of these experimental observations, it has been introduced the concept of synapsopathies, a notion describing brain disorders of synaptic function and plasticity. A close correlation between neurological diseases and synaptic abnormalities is especially relevant for those syndromes including also mental retardation in their symptomatology, such as Rett Syndrome (RS). RS (MIM312750) is an X-linked dominant neurological disorder that is caused, in the majority of cases by mutations in methyl-CpG-binding protein 2 (MeCP2). This review will focus on the current knowledge of the synaptic alterations produced by mutations of the gene MeCP2 in mouse models of RS and will highlight prospects experimental therapies currently in use. Different experimental approaches have revealed that RS could be the consequence of an impairment in the homeostasis of synaptic transmission in specific brain regions. Indeed, several forms of experience-induced neuronal plasticity are impaired in the absence of MeCP2. Based on the results presented in this review, it is reasonable to propose that understanding how the brain is affected by diseases such as RS is at reach. This effort will bring us closer to identify the neurobiological bases of human cognition.